Osteoid Osteoma of the Great Toe Mimicking Osteomyelitis: A Case Report and Review of the Literature. (28th August 2013) - Turkmen, Ismail; Alpan, Bugra; Soylemez, Salih; Ozkan, Feyza Unlu; Unay, Koray; Ozkan, Korhan
Abstract : Osteoid osteomas are well-known benign tumors, seen generally in long bones. When seen in phalanxes or toes, they can cause a diagnostic dilemma. A young male presented to us with complaints of enlargement of the great toe and severe pain. He had had an ingrown toe-nail operation before, and this situation caused a diagnostic dilemma. In this case report, we emphasize that osteoid osteomas can cause diagnostic dilemmas and it should be kept in mind as a differential diagnosis.